2016
DOI: 10.15376/biores.11.2.4663-4676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Number of UV-Protective Coats on the Color Stability and Surface Defects of Painted Black Locust and Norway Spruce Woods Subjected to Natural Weathering

Abstract: This paper utilized 12 coating systems, based on an acrylate and a hydrophobic polymer, with the addition of light pigments, nano-sized polyvalent metal (AsS-chelate complex) for ultraviolet protection, and iodopropynyl butylcarbamate fungicide. This study deals with the impact of the number of coats on the color stability and the surface defects of painted black locust (Robinia pseudoacacia L.) and Norway spruce (Picea abies Karst L.) woods after up to three years of natural weathering, at a slope of 45°. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
4
7
0
Order By: Relevance
“…The results of the experiment in this work confirmed that application of the top hydrophobic layer can extend the overall durability of coating systems on oak wood as well as on other wood species [25,27,29]. However, it is necessary to apply a suitable hydrophobic layer to a specific coating system because the resulting effect differs (Figures 5 and 6).…”
Section: Final Discussion Of Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The results of the experiment in this work confirmed that application of the top hydrophobic layer can extend the overall durability of coating systems on oak wood as well as on other wood species [25,27,29]. However, it is necessary to apply a suitable hydrophobic layer to a specific coating system because the resulting effect differs (Figures 5 and 6).…”
Section: Final Discussion Of Resultssupporting
confidence: 74%
“…Another use of hydrophobic coatings is their application as a topcoat to prevent the synergistic action of solar radiation and water [25,26]. In previous studies [27][28][29], the efficiency of a top hydrophobic coating to prolong the overall service life of a coating system applied on Norway spruce and Black locust wood was proved.…”
Section: Introductionmentioning
confidence: 99%
“…Leaching occurs when wood is exposed to weathering in the native state, or if the continuous protective coating layer is damaged [16]. In the case of natural weathering in the exterior, the wood subsequently turns gray (decrease of L*, a*, b*) due to the deposition of dirt and the effects of moulds or wood-staining fungi [20,72]. These subsequent changes do not occur during artificial weathering in a UV-chamber with demineralized water and a pure indoor environment, and only an overall colour loss on the exposed wood surfaces takes place [70].…”
Section: Resultsmentioning
confidence: 99%
“…When exterior oil-based coating (C) is applied, a longer service life can be expected in the case of softwoods [79] that have a morphological structure that is more simple than hardwoods with wide open vessels [57]. However, each underlying wood can affect the service life of the coating individually through the specific content of the extractives [27], and it is therefore necessary to confirm these assumptions by testing and comparing the evaluated characteristics [20,23,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation